Perancangan Sistem Informasi Penjualan Motor Bekas Berbasis Web pada Zidan Jaya Motor - Rila Kurniawan; Heri Mulyono; irsyadunas irsyadunas (STKIP PGRI Sumatera Barat, 2021)
Zidan Jaya Motor is a company that serves the sale and purchase of used motorcycles, from various brands and types of motorcycles. The problem that is often encountered is the ineffectiveness of sales services in terms of time and effort because they still use manual data collection in the company's parent book. The purpose of this research is to design a web-based used motorcycle sales application. This sales information system planning uses the SDLC (system development life cycle) development method with the PHP (hypertext markup language) programming language. This sales application makes it easy for Zidan Jaya Motor to manage goods data, sales reports, optimize services and maintain company data security. With the support of human resources and computerized information systems.